1999
DOI: 10.1046/j.1365-2249.1999.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful immunomodulating in AIDS patients with ursodeoxycholic acid—a pilot study

Abstract: SUMMARYBased on the positive therapeutic results with ursodeoxycholic acid (UDCA) in patients with primary biliary cirrhosis, in whom we observed a clinical improvement in conjunction with the normalization of the low pretreatment dipeptidyl peptidase (DPIV, CD26) expression of peripheral blood lymphocytes (PBL), we hypothesized that the very low DPIV expression in AIDS patients could be positively in¯uenced by UDCA. Four young male AIDS patients were therefore treated with 750 mg of UDCA for 4 months. The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…sDPP4 was quantified before infection (N = 87), in primary HIV infection (PHI, N = 36), at three months post‐seroconversion (M3, N = 126) and six months post‐seroconversion (M6, N = 104). In most studies, the levels of sDDP4 are measured at the level of its enzymatic activity and absolute concentrations are more rarely presented . We measured both and as in previous studies , found a strong correlation between the concentration and enzymatic activity of sDDP4 ( R = 0.72, p < 0.0001 and Figure A).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…sDPP4 was quantified before infection (N = 87), in primary HIV infection (PHI, N = 36), at three months post‐seroconversion (M3, N = 126) and six months post‐seroconversion (M6, N = 104). In most studies, the levels of sDDP4 are measured at the level of its enzymatic activity and absolute concentrations are more rarely presented . We measured both and as in previous studies , found a strong correlation between the concentration and enzymatic activity of sDDP4 ( R = 0.72, p < 0.0001 and Figure A).…”
Section: Resultssupporting
confidence: 66%
“…DPP4 has been less studied in viral infections, with the exception of HCV . A study on HIV infection provided evidence that immunomodulation by Ursodeoxycholic acid can increase the number of CD4 + DPP4 + T cells in AIDS patients . Herein, we have studied for the first time sDPP4 levels in primary HIV infection, demonstrating that sDPP4 is severely decreased during PHI in two independent cohorts.…”
Section: Discussionmentioning
confidence: 85%
“…PCS is a microbial metabolite that is closely related to uremia and is the most common substance during uremia [47]. At excessive levels, PCS can increase renal fibrosis, decrease uric acid excretion by the kidneys, and stimulate uric acid accumulation, which can induce gout [48]. m–Methyl hippuric acid, also known as 3–methyl propionate, is an organic N–acyl–alpha amino acid synthesized from hippuric acid.…”
Section: Discussionmentioning
confidence: 99%
“…UDCA may have both cytoprotective and immunological effects, also in HIV-infected subjects [74]. To date, the role of UDCA treatment for NASH has been evaluated only in HIV-negative population.…”
Section: Drug Therapy For Nashmentioning
confidence: 99%